Experiences, expectations and preferences regarding MRI and mammography as breast cancer screening tools in women at familial risk. (April 2021) - Geuzinge, H. Amarens; Heijnsdijk, Eveline A.M.; Obdeijn, Inge-Marie; de Koning, Harry J.; Tilanus-Linthorst, Madeleine M.A.; ,
Abstract: Background: Several studies have investigated MRI breast cancer screening in women at increased risk, but little is known about their preferences. In this study, experiences, expectations and preferences for MRI and mammography were evaluated among women undergoing screening with MRI and/or mammography in the randomized FaMRIsc trial. Methods: A 17-item questionnaire was sent to 412 women in the FaMRIsc trial. Participants were aged 30–55 years, had a ≥20% cumulative lifetime risk, but no BRCA1/2 or TP53 gene variant, and were screened outside the population-based screening program. Women received annual mammography (mammography-group), or annual MRI and biennial mammography (MRI-group). We asked whether women trust the screening outcome, what they consider as (dis)advantages, which screening they prefer and what they expect of the early detection by the screening tools. Results: 255 (62%) women completed our questionnaire. The high chance of early cancer detection was the most important advantage of MRI screening (MRI-group: 95%; mammography-group: 74%), while this was also the main advantage of mammography (MRI-group: 57%; mammography-group: 72%). Most important disadvantages of MRI were the small tunnel and the contrast fluid (for 23–36%), and of mammography were its painfulness and X-radiation (for 48–60%). Almost the whole MRI-group and half the mammography-group preferred screening with MRI (either alone or with mammography). Discussion: Most women would prefer screening with MRI. The way women think of MRI and mammography is influenced by the screening strategy they are undergoing. Our outcomes can be used for creating information brochures when MRI will be implemented for more women. Highlights: Women consider the small tunnel and contrast fluid important disadvantages of MRI. How women think of MRI is influenced by the screening strategy they are undergoing. Most women with a family history of breast cancer prefer screening with MRI.